ANALISIS PEMAKAIAN SENSOR LOADCELL DALAM PERHITUNGAN BERAT BENDA PADAT DAN CAIR BERBASIS MICROCONTROLLER - Agus Wibowo; Lawrence Adi Supriyono (STEKOM PRESS, 2019)
The development of microcontroller technology that is rapidly making applications to be developed as a work in the field of technology that can help and facilitate human activities. Researchers see that current technological developments there are many uses of loadcell sensors to detect weight on objects. The number of factors that affect the weight difference between digital scales and scales very significant conventional. Therefore researchers analyzed the use of loadcell sensors for calculate solid and liquid objects and analyze the work system and the accuracy of the accuracy on the loadcell sensor in calculating the weight of solid objects and liquid objects.